New discovery of Opuntia humifusa (Cactaceae) in the vicinity of Kyiv (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
Data on a new finding of Opuntia humifusa (Raf.) Raf. (Cactaceae A.L. Juss.) in mainland Ukraine (near Khodosivka village, Obukhiv district Kyiv region) are presented. The newly discovered location is described small populations of the species. The number of detected locations within the population – 5, and the number of found specimens – 11 were given. The age spectra of individuals in O. humifusa population were characterized. The predominate age states are generative – 45.5 %, what indicates the successful acclimatization and naturalization of the species in the forest-steppe zone of Ukraine. Geobotanical descriptions have been made and syntaxonomic features of O. humifusa habitats have been described. Individuals of this species typical of steep moving clay slopes in tract “Planer Mountain” where they belong to the groups of classes Festuco-Brometea Br.-Bl. et Tx. in Br.-Bl. 1949 and Artemisietea vulgaris Lohmeyer, Preising et R.Tüxen ex von Rochow 1951. Vegetation of ruderalized steppe habitats of O. humifusa is floristically depleted with sparse grassland. The population is on moving slopes (angle of inclination up to 35–40°) on which erosion processes took place. The total projective coverage varies from 50 to 90 %, decreasing on steep slopes and increasing on gentle slopes. Assumptions about the probable way of O. humifusa diaspores drift in the vicinity of Kyiv and the ways of its expansion from south to north are specified. The priority of O. humifusa seed reproduction due to anthropochor transfer is indicated. Ways of this species acclimatization to different regions of mainland Ukraine, naturalization into natural steppe phytocenoses of the steppe zone and distribution in natural plant groups of the forest-steppe zone are demonstrated. Given the current climate changes, this invasive species needs further monitoring on its spread throughout Ukraine with the development of appropriate preventive measures.
Keywords: invasion, forest-steppe zone, naturalization, Opuntia, phytocenosis, steppe zone.